Pelatihan Menggambar Dengan Teknik Menggambar Perspektif Pada SMK Negeri 9 Medan - Muhammad Sabri; Titin Setiawati; Ahmad Chairyan (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2023)
Perspective or point of view is a technique or method for drawing objects in the form of objects, rooms (interiors), and environments (exteriors) that are larger in size than humans. This technique was created due to the limited visibility of our eyes in seeing objects. The farther the eye can see, the smaller it appears and will even disappear from view at a certain distance. Conversely, the closer our eyes look, the object will appear bigger. Two things must be used as a benchmark in perspective drawing techniques. Perspective in general means images that are used to communicate objects in the form of objects, spaces, environments that are visible to the human eye on a flat plane. Perspective drawing is an image that technically uses a vanishing point. Perspective drawing itself is a form of 3-dimensional images.